Robotic Engineering as an Innovative Direction of Developing the Design Culture of Students (Eurasian Journal of Learning and Academic Teaching, 2022)
This article talks about the role of robotics and its use in developing the design culture of schoolchildren. Also, information about the necessary conditions for the use and application of robotics was mentioned in the educational process.